"Chasing the High" - Experiences of Ethylphenidate as Described on International Internet Forums - Christophe Soussan; Anette Kjellgren (SAGE Publishing, 2015)
Ethylphenidate is a novel psychoactive substance with undocumented effects, risks, and motivation for use. In this study, we investigated the experience of ethylphenidate by analyzing self-reports published on Internet forums, which revealed seven overarching themes: (1) compulsive redosing and addiction; (2) impacts on the mental state; (3) bodily agitation; (4) increased sociableness; (5) administration; (6) diverse evaluations based on intention; and (7) safety and precaution. Ethylphenidate appeared as a potent psychostimulant with an imminent abuse potential. It was mainly used for recreational purposes. The effects included not only pleasurable stimulation, euphoria, and cognitive enhancement but also indecisiveness, anxiety, and cognitive fragmentation. The users reported an increase in body temperature, heart rate, and blood pressure, but they also experienced profuse sweating and muscle tension. Ethylphenidate acted as a social lubricant, enhancing intimacy, communication, and social skills. Two opposing user mentalities were uncovered: (1) pleasure seeking and risk neglecting, and (2) safety-first orientation. This information could be of importance to legislators, public health personnel, and prevention strategists.